Cover Image. (30th March 2018) - Bahadorikhalili, Saeed; Ashtari, Arsalan; Ma'mani, Leila; Ranjbar, Parviz Rashidi; Mahdavi, Mohammad
Abstract : The cover image, by Saeed Bahadorikhalili et al., is based on the Full Paper Copper‐supported β‐cyclodextrin‐functionalized magnetic nanoparticles: Efficient multifunctional catalyst for one‐pot 'green' synthesis of 1, 2, 3‐triazolylquinazolinone derivatives, DOI:10.1002/aoc.4212 .